Right Atrial Appendage Thrombus in Atrial Fibrillation: A Case Report and Review of the Literature - Aaron C. Richardson DO; Michael Omar MD; Gladys Velarde MD; Emil Missov MD, PhD; Robert Percy MD; Srinivasan Sattiraju MD (SAGE Publishing, 2021)
Atrial fibrillation (Afib) is the most common abnormal heart rhythm in adults and has become a significant public health concern affecting 2% to 3% of the population in Europe and North America. Left atrial appendage (LAA) thrombi is the source of 90% of left-sided cardiac thrombi in patients with Afib, which can cause stroke and other systemic vascular events. Right atrial appendage (RAA) thrombi formation in Afib is much less common but complications include pulmonary embolism or paradoxical migration across patent foramen ovale with risk of systemic embolization. The prevalence and subsequent clinical complications of RAA thrombi formation in Afib patients is not well understood. Management of RAA thrombi should be similar to that of LAA thrombi which includes delaying cardioversion and anticoagulating with warfarin therapy to achieve international normalized ratio of 2 to 3.